VIBRATIONS DETECTION IN INDUSTRIAL PUMPS BASED ON SPECTRAL ANALYSIS TO INCREASE THEIR EFFICIENCY - Belhadef RACHID; Ahmed HAFAIFA; Mohamed BOUMEHRAZ (Management Systems in Production Engineering, 2016)
Spectral analysis is the key tool for the study of vibration signals in rotating machinery. In this work, the vibration analy-sis applied for conditional preventive maintenance of such machines is proposed, as part of resolved problems related to vibration detection on the organs of these machines. The vibration signal of a centrifugal pump was treated to mount the benefits of the approach proposed. The obtained results present the signal estimation of a pump vibration using Fourier transform technique compared by the spectral analysis methods based on Prony approach.